DESAPROPRIAÇÃO PARA A CRIAÇÃO DE UNIDADES DE CONSERVAÇÃO: UM ESTUDO DE CASO DA IMPLANTAÇÃO DO PARQUE NACIONAL DOS CAMPOS GERAIS PONTA GROSSA 2008 - Manarim, Sulimar Kellie (2008)
With the environmental degeneration the society needs to think its concepts over. Considering that the scarceness of the natural resources come from the modern system for wealth production, the nature degeneration reversion involves a much deeper changing in the social structure than it can look in a first moment. In order to have a consistent ecological equilibrated environment is necessary to have the institutes, already insert in the society, changed. The profit taking, the wealth distribution, the value for the use of things, besides the property, need to be faced under a new outlook. Only with the guarantee of a minimum income, able to guarantee conditions so that all humans with no exceptions have conditions of a decent life, then the environmental preservation will be established. The conscience about the preservation need is something that will be only possible when the most part of the population have no worries with basics needs. For this, the antropocentric model needs to be replaced by a conception that respects the human dignity. Among the new models that are coming up, the one that has stand out the most is the biocentric, for according to its focus, the human being is inserted in the life web, owning respect to all other nature creatures including other human beings. For this, the property relativity is inevitable. Nevertheless, the property is inserted in the social structure and the Brazilian population is not mature enough to promote the necessary standardized change. That’s why, is a due to the state to conduct this change. In the current study, the state attitude toward the consolidations of the biocentric model was observed. It was analyzed the installation of the National Park of Campos Gerais, laid in the city of Ponta Grossa, and in Castro and Carambeí counties. The research is concentrated in Ponta Grossa, where more than the half of the Unit of Conservation is located, besides being a local that contains several private properties, whose owners belong to the local elite. Toward this, its evident the dispute for power and the found for the property institute. This way, there’s an urge of the state intervention, so that the collectivity is not damaged with the influence of some groups toward the local leaderships. Facing this barrier between the right to the property and the right to a ecological equilibrated environment, the second one must prevail, under the argument that the public interests must overcome private interests. The Federal constitution provides ways to the state to accomplish the environmental preservation, toward a reasonably proportion between anthropocentrism and biocentrism in its texts. The environmental preservation doe not imply, only, in the defense of the natural resources, but also of the humanity, that needs to be rescued from the ignorance caused by the system of wealth production, coming from the industrialization.